2014
DOI: 10.1002/2014gl059647
|View full text |Cite
|
Sign up to set email alerts
|

On the relation between explosive cyclones affecting Europe and the North Atlantic Oscillation

Abstract: Intense winter cyclones often lead to hazardous weather over Europe. Previous studies have pointed to a link between the North Atlantic Oscillation (NAO) and strong European windstorms. However, the robustness of this relation for cyclones of varying intensities remains largely unexplored. In this paper, the bi-directional relation between the NAO and cyclones impacting Europe is analyzed for the period 1950-2010 focusing on the sensitivity to storm intensity. Evidence is given that explosive (EC) and non-expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 23 publications
(51 reference statements)
1
18
0
2
Order By: Relevance
“…A positive NAO favours the occurrence of cyclones across the North Atlantic14 and destructive surface winds over continental Europe15. Indeed, we find a match between low instaneous dimensions and historical storms: the names and dates of storms corresponding to minima of d ( ζ ) are reported in Fig.…”
supporting
confidence: 51%
“…A positive NAO favours the occurrence of cyclones across the North Atlantic14 and destructive surface winds over continental Europe15. Indeed, we find a match between low instaneous dimensions and historical storms: the names and dates of storms corresponding to minima of d ( ζ ) are reported in Fig.…”
supporting
confidence: 51%
“…Statistically significant increases in destructiveness rates are found at both positive and negative lags; the peak composite PDI value exceeds 11% (Figure 2c). We note that this value is well in excess of that associated with the positive NAO (Table 1), which is often linked to enhanced storminess over the Atlantic [e.g., Gómara et al, 2014b]. The origin of the double peak in the PDI index is discussed in detail in Text S6.…”
Section: Dynamical Evolution Of North American Cold Spells and Impactmentioning
confidence: 79%
“…Cold temperatures over North America and storms affecting Europe are often discussed in the context of the Pacific-North American Pattern (PNA) and the NAO [e.g., Leathers et al, 1991;Gómara et al, 2014b]. Here we investigate whether the large-scale patterns and anomaly fields discussed in section 3 are the direct results of strong projections on either of these variability patterns.…”
Section: Relation With Large-scale Modes Of Variabilitymentioning
confidence: 99%
“…In view of this, one might naively expect DWB to have a strong connection with the leading mode of climate variability in the region, namely, the NAO. The NAO has been repeatedly investigated as a major driver of both Atlantic storminess and jet stream anomalies [e.g., Woollings and Blackburn , ; Pinto and Raible , ; Gómara et al , ]. It has also been interpreted as the outcome of specific WB configurations [e.g., Benedict et al , ; Franzke et al , ; Riviere and Orlanski , ; Strong and Magnusdottir, , ; Kunz et al , ; Drouard et al , ], and WB frequency over localized regions of the North Atlantic has been found to account for a very high fraction of both the interannual and intraseasonal NAOI variability [ Strong and Magnusdottir , ].…”
Section: Discussionmentioning
confidence: 99%
“…The DWB described in section 3 is a large‐scale process, with individual events spanning a vast stretch of the North Atlantic basin. Previous studies have suggested that the occurrence of Rossby wave breaking, especially if associated with a positive NAO, has a strong influence on the jet stream [ Riviere and Orlanski , ; Gómara et al , ; Pinto et al , ]. As discussed in section 1, DWB will generally lead to an increased meridional PV gradient in the region between the breakings and to an intensified midlatitude jet.…”
Section: Double Wave Breaking and The Jet Streammentioning
confidence: 99%